Epidemiologic and clinic characteristics of patients with chronic simple glaucoma - Yargelis González Orza; Tania Yelina Silva Chil; Lidice Quiala Alayo; Marileidis Reynoso Bravo; Yisenia Quintana Lahens (Medisan, 2023)
Introduction: Glaucoma is one of the most prevalent eye diseases worldwide and is characterized by high intraocular pressure, changes in the papilla and visual field alterations.